Kaum Muda dalam The Social Dilemma: Sebuah Refleksi Kritis tentang Narasi Kerja, Waktu Luang dan Subjektivitas di Era Post-Fordist - Gregorius Ragil Wibawanto (Universitas Gadjah Mada, 2021)
This article presents a reflection on the constitutive relation of youth, work, and leisure in post-Fordist society using a documentary film The Social Dilemma as an entry point. The film has been praised as successful in delivering critics toward digital capitalism. Its content builds upon the idea that the political economy of giant platforms have caused serious problems on the vulnerability of young people’s wellbeing and their precarity of work. Different from previous comments, this article argues that The Social Dilemma does not only convey critique of digital capitalism and youth’s wellbeing, but also represents a relational narrative of work-leisure among young people in post-Fordist society, which is exploitative in its character. Building upon previous studies on youth, work, leisure, and subjectivity this article tries to offer a critical reflection—based on the respective film—that digital arena in the post-Fordist context has created a transformation of leisure into labour. This transformation has further produced a binary subjectivity cultivated by the biopolitical power of immaterial labour through massive digital infrastructure that serve as the main characteristic of post-Fordist society.